Analisis Efisiensi dengan Metode Data Envelopment Analysis (DEA) pada Lembaga Amil Zakat Muhammadiyah - Lian Fuad (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2023)
One form of effort to improve the quality of institutional management is to measure the achievement of targets that have been planned. Achievement will be efficient if the input as institutional capital in running the institution makes a small contribution but gets the maximum output. The purpose of this research was to determine the efficiency level of the Amil Zakat Muhammadiyah Institute for the 2017-2020 period using the Data Envelopment Analysis (DEA) method with the Assumption of Constant Return of Scale (CRS) with input orientation. Research variabels use input and output. The input variabel component is operational costs. Personnel costs, outreach costs, and total assets. While the output variabel components are receipt of ZIS funds and distribution of ZIS funds. The results showed that in all periods from 2017-2020, efficiency performance was 100% or 1. But in 2019, Lazismu's efficiency performance earned a value of 0.977.